Cytogenetic studies on three species of primates in Malaysia - Bongso, Tuan Ariffeen; Hilmi, M. (Malaysian Society of Applied Biology, 1981)
Chromosome number and morphology of Macaca fascicularis, Presby tis melalophos, Hylobates lar and a % M. fascicularis x % M. nemestrina hybrid were studied using the leukocyte culture method. The macaques originated from the North and South parts of Peninsula Malaysia. M. fascicularis and the hybrid showed diploid numbers of 42 chromosomes, while P. melalophos and H. lar showed 44 chromosomes respectively. Differences in individual chromosome morphology were observed between the three species. Two distinct satellite chromosomes was observed in all species. However, 70% of metaphases in H. lar showed two conspicuous satellite chromosomes, while 30% of metaphases showed one satellite chromosome. In M. [ascicularis and P. melalophos 50% of metaphases showed two satellite chromosomes and 50% of metaphases contained one satellite chromosome. The Y chromosome was different in morphology between the three species. The Y chromosome of H. lar was a very small submetacentric chromosome, whereas in P. melalophos it was acrocentric and in M. fascicularis it was a fairly large submetacentric chromosome. A translocation probably of the Robertsonian type was observed in one M. fascicularis. This animal had a previous history of abortions and stillbirths.